A novel mutation in an adolescent presenting with growth and pubertal delay - Maria-Christina Antoniou; Thérèse Bouthors; Cheng Xu; Franziska Phan-Hug; Eglantine Elowe-Gruau; Sophie Stoppa-Vaucher; Almer van der Sloot; James Acierno; Daniele Cassatella; Celine Richard; Andrew Dwyer; Nelly Pitteloud; et al. (Korean Society of Pediatric Endocrinology, 2019)
Mutations in the CHD7 gene, encoding for the chromodomain helicase DNA-binding protein 7, are found in approximately 60% of individuals with CHARGE syndrome (coloboma, heart defects, choanal atresia, retarded growth and development, genital hypoplasia, ear abnormalities and/or hearing loss). Herein, we present a clinical case of a 14-year-old male presenting for evaluation of poor growth and pubertal delay highlighting the diagnostic challenges of CHARGE syndrome. The patient was born full term and underwent surgery at 5 days of life for bilateral choanal atresia. Developmental milestones were normally achieved. At age 14 his height and weight were -2.04 and -1.74 standard deviation score respectively. He had anosmia as well as prepubertal testes and micropenis (4 cm×1 cm). The biological profile showed low basal serum testosterone and gonadotropins (testosterone, 0.2 nmol/L; luteinizing hormone, 0.5 U/L; follicle-stimulating hormone, 1.3 U/L), and otherwise normal pituitary function and normal imaging of the hypothalamic-pituitary area. The constellation of choanal atresia, anosmia, mild dysmorphic features, micropenis and delayed puberty were suggestive of CHARGE syndrome. Targeted genetic testing of CHD7 was performed revealing a de novo heterozygous CHD7 mutation (c.4234T>G [p.Tyr1412Asp]). Further paraclinical investigations confirmed CHARGE syndrome. Despite the presence of suggestive features, CHARGE syndrome remained undiagnosed in this patient until adolescence. Genetic testing helps clarify the phenotypic and genotypic spectrum to facilitate diagnosis, thus promoting optimal follow-up, treatment, and appropriate genetic counselling.